2017
DOI: 10.1186/s13047-016-0178-x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical shape models of cuboid, navicular and talus bones

Abstract: BackgroundThe aim was to develop statistical shape models of the main human tarsal bones that would result in novel representations of cuboid, navicular and talus.MethodsFifteen right and 15 left retrospectively collected computed tomography data sets from male individuals, aged from 17 to 63 years, with no known foot pathology were collected. Data were gathered from 30 different subjects. A process of model building includes image segmentation, unifying feature position, mathematical shape description and obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 74 publications
(75 reference statements)
1
29
0
Order By: Relevance
“…To overcome the above issues, SSM has been proposed as a promising way to describe shapes with geometric similarities, so it is appropriate for bones like the talus (Sarkalkan et al, 2014 ; Ambellan et al, 2019 ). Melinska et al ( 2017 ) developed SSMs of the cuboid, navicular, and talus bones using the spherical harmonics based on 30 subjects and showed the clinical potential of SSM in representing tarsal bones. Feng et al ( 2018 ) compared the talus bones in clubfeet and in normal feet through two methods: direct measurement and SSM; both approaches revealed differences between normal feet and clubfeet.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the above issues, SSM has been proposed as a promising way to describe shapes with geometric similarities, so it is appropriate for bones like the talus (Sarkalkan et al, 2014 ; Ambellan et al, 2019 ). Melinska et al ( 2017 ) developed SSMs of the cuboid, navicular, and talus bones using the spherical harmonics based on 30 subjects and showed the clinical potential of SSM in representing tarsal bones. Feng et al ( 2018 ) compared the talus bones in clubfeet and in normal feet through two methods: direct measurement and SSM; both approaches revealed differences between normal feet and clubfeet.…”
Section: Introductionmentioning
confidence: 99%
“…SSMs are a powerful tool used in the analysis of regional anatomical variability of a structure [38, 41]. SSMs have previously been employed in skeletal [3742], vascular [44–47], and neurological research [43]. Moreover, recent studies have indicated that SSMs can be a useful tool in pre-operative planning, specifically in bony reconstructions such as in craniomaxillofacial surgeries [55, 56].…”
Section: Discussionmentioning
confidence: 99%
“…A SSM is calculated from a database of samples to form a model with a mean shape and several modes of variation [37]. Previous studies have utilized SSMs to study the variability of bony structures [3742], neurological structures [43], and blood vessels [44–47], however to our knowledge, SSMs have not yet been employed to study SS anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…16 Limited studies have conducted SSM in bones of the foot and ankle. [17][18][19] Moreover, studies to date lacked clinical or anatomical interpretation of the mathematical modes of variation and did not consider joint coverage, space, or congruency. An SSM-based approach to characterizing subtalar joint morphometrics could lead to greater insight and advancements in the clinical treatment of hindfoot disorders (eg, ankle joint OA and flatfoot deformity).…”
Section: Introductionmentioning
confidence: 99%